'Breath, Belief, Focus, Touch': Applied puppetry in simulated role-play for person-centred nursing education. Issue 1 (1st July 2020) - Tizzard-Kleister, Karl; Jennings, Matt
As a subject area that sustains itself on the productive tension between human and non-human agency, applied puppetry is a pragmatic and compelling approach to considering the role of objects in an anthropocentric world. In health care, mannequins play the role of simulated patients. Most often, they simply stand in for the body of the patient. However, this misses the potential that the materiality of these objects holds when considered through applied puppetry terms. This article examines examples of puppetry used in simulated role-play (SRP) for training and assessment, including a specific project involving applied puppetry with person-centred nursing (PCN) students at Ulster University (UU). It attempts to theorize how, when used in this way, applied puppetry is a metaphorical and translational act of anthropomorphism – a process by which an object can 'become' more than a thing. In this context, we seek to define a practice in which a mannequin fulfils its potential as a puppet-patient in SRP for PCN students.